Beyond the Global Crisis : Structural Adjustments and Regional Integration in Europe and Latin America. - Punzo, Lionello F. (Routledge studies in the modern world economy., 2012)
The book aims at offering a comparative, multi-perspective analysis of the different, at times parallel, at times with varying degrees of interdependence, macroeconomic and structural adjustments in the two continents against the backdrop of important processes of regional integration. Its reading offers a multifaceted appreciation of the reality emerging from the mixing up of longer run tendencies deepened by the brute force of the financial and then industrial crisis.